2019
DOI: 10.1123/ijsnem.2018-0288
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Illness and Inflammation: Can Immunonutrition and Iron Help?

Abstract: The main focus of this review is illness among elite athletes, how and why it occurs, and whether any measures can be taken to combat it or to prevent its onset. In particular, there is particular interest in exercise-induced immunodepression, which is a result of the immune system regarding exercise (e.g., prolonged, exhaustive exercise) as a challenge to its function. This promotes the inflammatory response. There is often a high incidence of illness in athletes after undertaking strenuous exercise, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 51 publications
(55 reference statements)
1
40
1
Order By: Relevance
“…1 Meta-analysis for association studies for HFE gene and endurance sports 3-11% of male athletes) (Fallon 2008;Malczewska et al 2001;Parks et al 2017) with higher frequency in endurance athletes, e.g., distance runners and triathletes (Rietjens et al 2002;Lukaski 2004;Sinclair and Hinton 2005), and physically active individuals compared with sedentary controls (Milic et al 2011;Eliakim et al 2002;Gropper et al 2006;Woolf et al 2009). Factors, which could affect both male and female athletes' iron stores, is low energy intake, inadequate dietary iron intake, vegetarian diets, exercise-associated iron losses, reduced iron recycling (Hinton 2014;Castell et al 2019;Sim et al 2019), and menstrual blood losses in female athletes (Pedlar et al 2018). Iron deficiency, which is accompanied by a reduction of oxygen transport to the working skeletal muscle, can lead to lower blood pH, depletion of muscle glycogen, which may negatively affect the endurance performance and exercise economy (Sim et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…1 Meta-analysis for association studies for HFE gene and endurance sports 3-11% of male athletes) (Fallon 2008;Malczewska et al 2001;Parks et al 2017) with higher frequency in endurance athletes, e.g., distance runners and triathletes (Rietjens et al 2002;Lukaski 2004;Sinclair and Hinton 2005), and physically active individuals compared with sedentary controls (Milic et al 2011;Eliakim et al 2002;Gropper et al 2006;Woolf et al 2009). Factors, which could affect both male and female athletes' iron stores, is low energy intake, inadequate dietary iron intake, vegetarian diets, exercise-associated iron losses, reduced iron recycling (Hinton 2014;Castell et al 2019;Sim et al 2019), and menstrual blood losses in female athletes (Pedlar et al 2018). Iron deficiency, which is accompanied by a reduction of oxygen transport to the working skeletal muscle, can lead to lower blood pH, depletion of muscle glycogen, which may negatively affect the endurance performance and exercise economy (Sim et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…• To treat deficiency or suboptimal status, use intravenous or intramuscular iron supplements but only under medical supervision Note. Adapted from Castell et al (2019). Vol.…”
Section: Recognizing the Special Issues Of Event Groups In Athletesmentioning
confidence: 99%
“…Regarding illness, there is strong evidence to suggest that immunodepression can occur as a result of strenuous exercise (Castell et al, 2019;Peake et al, 2017), and a high incidence of upper respiratory tract illness is frequently reported (Drew et al, 2018;Nieman, 1994), before and particularly after endurance events. Low-energy availability has been identified as a key nutritional factor in such illness (Drew et al, 2018;Heikura et al, 2018); however, the provision of nutritional supplements to alleviate exercise-induced immunodepression and to aid more rapid recovery in athletes has also been well studied.…”
Section: Therapeutic Nutritional Supplements and Prophylactic Aidsmentioning
confidence: 99%
“…Glutamine and branched chain amino acids, which are often marketed to support bodybuilding and postexercise recovery, also have an unclear role in supporting immune function in athletes (Bermon et al, 2017). Clearly, immunonutrition is an emerging and important area for consideration in the use of dietary supplements for athlete populations, and as such, the reader is directed to recent reviews in this area (Bermon et al, 2017;Castell et al, 2019), in addition to the comprehensive paper on feeding the immune system (Calder, 2013).…”
Section: Therapeutic Nutritional Supplements and Prophylactic Aidsmentioning
confidence: 99%